Human SEC13Rp functions in yeast and is located on transport vesicles budding from the endoplasmic reticulum (The Rockefeller University Press, 1995)
In the yeast Saccharomyces cerevisiae, Sec13p is required for intracellular protein transport from the ER to the Golgi apparatus, and has also been identified as a component of the COPII vesicle coat structure. Recently, a human cDNA encoding a protein 53% identical to yeast Sec13p has been isolated. In this report, we apply the genetic assays of complementation and synthetic lethality to demonstrate the conservation of function between this human protein, designated SEC13Rp, and yeast Sec13p. We show that two reciprocal human/yeast fusion constructs, encoding the NH2-terminal half of one protein and the COOH-terminal half of the other, can each complement the secretion defect of a sec13-1 mutant at 36 degrees C. The chimera encoding the NH2-terminal half of the yeast protein and the COOH-terminal half of the human protein is also able to complement a SEC13 deletion. Overexpression of either the entire human SEC13Rp protein or the chimera encoding the NH2-terminal half of the human protein and the COOH-terminal half of the yeast protein inhibits the growth of a sec13- 1 mutant at 24 degrees C; this growth inhibition is not seen in a wild- type strain nor in other sec mutants, suggesting that the NH2-terminal half of SEC13Rp may compete with Sec13-1p for a common target. We show by immunoelectronmicroscopy of mammalian cells that SEC13Rp (like the putative mammalian homologues of the COPII subunits Sar1p and Sec23p) resides in the region of the transitional ER. We also show that the distribution of SEC13Rp is not affected by brefeldin A treatment. This report presents the first demonstration of a putative mammalian COPII component functioning in yeast, and highlights a potentially useful approach for the study of conserved mammalian proteins in a genetically tractable system.